INVESTIGATION OF METHYLATION AND EXPRESSION STATUS OF PAX1 GENE VIA EPIGENOMIC PROFILING IN ORAL MALIGNANT LESIONS - Arda Öztan; Gülsüm Ak; Murat Ulusan; Semra Demokan (Sabiad)
Introduction: Our previously study (TUBITAK-SBAG-114S497) showed hypermethylation of the PAX1 gene in Turkish oral squamous cell carcinoma (OSCC) patients via methylation-array results. In this study, we aimed to validate its potential as an epigenetic biomarker for OSCC by analyzing the methylation status and the changes in methylation-related gene expression of the PAX1 gene in Turkish OSCC patient and healthy groups. Material and Methods: Expression and methylation levels of PAX1 gene were analyzed by Quantitative Real Time-PCR and Quantitative Methylation Specific PCR methods respectively, in tissues and body-fluid samples of 30 OSCC patients and 30 healthy individuals. Results: The methylation rates of the PAX1 gene in matched-normal tissue, tumors, serum and saliva samples of OSCC patients were 50%, 73%, 40%, and 66%, respectively. The methylation rates of the PAX1 gene in normal mucosa, serum and saliva samples of healthy individuals were found to be 6%, 0 and 10%, respectively. In the malignant group, 59% patients in whom methylation was observed in the promoter region of the PAX1 gene in the tumor tissue was found to have decreased expression levels in the tumor tissues compared to the matched-normal tissues. Conclusion: DNA hypermethylation of PAX1 gene may play a role in oral carcinogenesis and may be used as an epigenetic biomarker.